Factors Affecting Low Academic Achievement of Open University's Students in Indonesia - Heri Wahyudi (LPPM Universitas Terbuka, 2021)
This research aims to analyze the factors that cause low student academic achievement. To achieve these objectives, this research used a survey design to collect data from respondents. Before the research, the researchers conducted a pre-survey interview technique to several respondents in order to obtain information to formulate a construct that will be analyzed as well as to determine the research instruments. This research was conducted in regional office Denpasar with students from Non-Pendas Program with low academic achievement as the respondents. There were 71 respondents with a response rate of 92.5%. Based on these results, there are some important things that can be concluded: Lack of motivation, lack of study time and no teaching materials are factors which lead to low academic achievement with low impact.Not following the online tutorial, not forming a study group, lack of test preparation and lack of enrichment of the materials are factors which lead to low academic achievement with quite high impact.Not supportive learning situation and the lack of study planning are the factors that lead to low academic achievement with low impact.